Building motivation and entrepreneurship spirit in the women farmer group of Bola Village - L.M. Azhar Sa'ban; La Ode Muhammad Arham; Nanda Hartawati; Jestino Andre Pratama (Universitas Muhammadiyah Magelang, 2024)
Increasing the entrepreneurial spirit among the Women Farmers Group (KWT) in Bola Village, Batuga District, South Buton Regency, is the aim of this Community Service (PKM). This activity employs the method of delivering materials and facilitating discussions on how to cultivate entrepreneurial motivation within the Bola Village Women's Farmer Group. The results of the activity indicate that participants have become more motivated to pursue entrepreneurship. Despite having hectic daily schedules, participants are equipped with the tools for future entrepreneurship. They have boosted coffee production and introduced innovations in processing coffee into value-added food products. The knowledge acquired from this activity is expected to offer deeper insights into entrepreneurial activities among the Bola Village Women's Farmer Group. Furthermore, it is anticipated that this activity will inspire individuals to persist in developing their businesses.